1990
DOI: 10.1111/j.1469-8137.1990.tb00498.x
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of spores of vesicular–arbuscular mycorrhizal fungi*

Abstract: SUMMARYStorage of spores of vesicular-arbuscular (VA) mycorrhizal fungi in soil at 5 °C is a common way of preserving these fungi. This method was satisfactory for Glomus intraradix Schenck & Smith but not for Gigaspora margarita Becker & Hall, Glomus mosseae (Nicol. & Gerd.) Gerdemann & Trappe, and Acaulospora longula Spain & Schenck. Preservation of spores at -60 to -70°C was examined. Cryoprotectants such as DMSO, glycerol, mannitol, and sucrose were ineffective using the freeze-damage sensitive species G. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 15 publications
1
9
0
1
Order By: Relevance
“…The general rules for storage of AM fungi in pot culture type media are that cool is better than warm, and dry is better than moist (Daft et al 1987;Douds and Schenck 1990b). Storage is not a great issue for on-farm production of inocula in the tropics since these inocula are intended for use upon completion of the production cycle.…”
Section: Post Inoculum Production Issues Storagementioning
confidence: 99%
“…The general rules for storage of AM fungi in pot culture type media are that cool is better than warm, and dry is better than moist (Daft et al 1987;Douds and Schenck 1990b). Storage is not a great issue for on-farm production of inocula in the tropics since these inocula are intended for use upon completion of the production cycle.…”
Section: Post Inoculum Production Issues Storagementioning
confidence: 99%
“…Cryoprotectants including glycerol and mannitol, commonly used in the preservation of various organisms (Smith & Onions, 1994), were shown to be ineffective both in this study and in another study with AM fungi (Douds & Schenck, 1990). Incubation of beads containing groups of four spores, for 1 and 2 d in 0n5 M sucrose and for 1 d in 0n5 M trehalose, had no detrimental effect on %PIB before cryopreservation.…”
Section: mentioning
confidence: 84%
“…Therefore a method of long-term storage appears essential. Procedures to store AM fungi for long periods were investigated by Douds & Schenck (1990). These authors observed that slow drying of pot culture soil followed by freezing the spores in situ was satisfactory for cryoprotection and cryopreservation at k60 to k70mC of several AM fungi belonging to Glomus, Gigaspora, Entrophospora, Acaulospora and Scutellospora.…”
Section: mentioning
confidence: 99%
“…However, sub-cultivation is being practiced for the maintenance [25][26][27] and contaminations risk is common problem [25]. Moreover, sub-cultivation is difficult or genetic variation may occur [28] and, genetic and physiological changes overtime cannot be prevented [29,25,30]. Thus, a method to maintain the viability, purity and stability of monoxenically produced AM fungal isolates over longterm storage periods is needed.…”
Section: Introductionmentioning
confidence: 99%